Local and Regional Breast Cancer Recurrences: Salvage Therapy Options in the New Era of Molecular Subtypes - Belkacemi, Yazid; Hanna, Nivin E.; Besnard, Clementine; Majdoul, Soufya; Gligorov, Joseph (Frontiers in Oncology, 2018)
Abstract Isolated local or regional recurrence of breast cancer (BC) leads to an increased risk of metastases and decreased survival. Ipsilateral breast recurrence can occur at the initial tumor bed or in another quadrant of the breast. Depending on tumor patterns and molecular subtypes, the risk and time to onset of metastatic recurrence differs. HER2-positive and triple-negative (TNG) BC have a risk of locoregional relapse between 6 and 8 times than luminal A. Thus, the management of local relapses must take into account the prognostic factors for the occurrence of metastases. It is important to personalize the overall management, including or not systemic treatment according to the metastatic risk. All isolated recurrence cases should be treated with curative intent. Complete surgical resection is recommended whenever possible. Patients who did not receive postoperative irradiation during their initial management should receive full-dose radiotherapy to the chest wall and to the regional lymph nodes if appropriate. Overall, total mastectomy is the "gold standard" among patients who were previously treated by conservative surgery followed by radiation therapy. In terms of systemic therapy, the benefits of additional treatments are not conclusively proven in cases of isolated recurrence. The beneficial role of chemotherapy has been reported in at least one randomized trial, while endocrine therapy and anti-HER2 are common practice. This review will discuss salvage treatment options of local and locoregional recurrences in the new era of BC molecular subtypes.